Study of the formation mechanism of gas hydrates of methane in the presence of surface-active substances - Bondarenko, Volodymyr; Svietkina, Olena; Sai, Kateryna (Eastern-European Journal of Enterprise Technologies, 2017)
The process of hydrate formation of methane in the presence of SAS in the temperature range of 274‒281 K was examined. The aim of the research conducted was to establish the effect of SAS on the process of GH formation, as well as to study kinetic features of their formation in the three-phase system “gas”‒”water+SAS”→”solid body (GH)”. We applied a stalagmometric method with automated photoelectron counting of drops (measurement error is 0.1 %), a conductometric method, with electrical conductivity measured using the Wheatson bridge (measurement error is 0.05–0.1 %). Interphase electric potential was measured by a potentiometric method using the potentiometer PPTV 1. Based on an analysis of the isotherms, by the indicators of surface tension of the aqueous solutions of SAS, we plotted isotherms of surface tension in the logarithmic –lgСSAS coordinates. The isotherms in the region of low concentrations demonstrate a curvilinear section, on which, in accordance with the Gibbs equation, adsorption at the interphase boundary increases with an increase in the concentrations. The curvilinear section of the isotherm passes into a straight line; in this case, the adsorption reaches its maximum value. Based on kink of the isotherm, we determined the value of CMC, which corresponds to the concentration of SAS equal to 1.75–2.00·10-2 mol/l. The addition of SAS leads to a decrease in the magnitude of CMC. While studying the mechanism of hydrate formation of methane in the presence of SAS, it was discovered that the hydrate formation mechanism includes the following stages: micellization and solubilization. However, an increase in the volume of absorbed methane in the presence of SAS, as well as the activation effect, indicate the micellar catalysis. It is shown that the presence of SAS increases the amount of gaseous methane in GH by several times, as well as improves its quality (friability).